Penguatan Halal Value Chain di Indonesia: Sinergi Pembiayaan Syariah, Sertifikasi Halal, dan Akses Pasar Ekspor - Jasri Jasri; Rafiqa Hastharita (CV. ITTC INDONESIA, 2026)
This article examines how Indonesia can strengthen its halal value chain by aligning Islamic financing, halal certification, and export market access. Using a qualitative scoping review of regulations, policy documents, and peer-reviewed studies, the paper synthesizes key bottlenecks and enabling factors across upstream–downstream activities, including compliance assurance, financing readiness, logistics integrity, and international recognition. The findings indicate that (1) mandatory halal certification creates stronger consumer trust but raises compliance and capacity challenges for MSMEs; (2) Islamic financial institutions can bridge working-capital and investment gaps when products are designed to fit halal industry characteristics and certification stages; and (3) export access depends on harmonization efforts, mutual recognition mechanisms, and trade facilitation that reduce non-tariff frictions. Policy implications include streamlining certification assistance, building halal traceability and logistics standards, and developing export-ready financing schemes to accelerate Indonesia’s role in the global halal ecosystem